Continuous dynamic recrystallization during severe plastic deformation. (November 2015) - Bacca, Mattia; Hayhurst, David R.; McMeeking, Robert M.
Graphical abstract: Highlights: A simple model for continuous dynamic recrystallization is proposed. Model validated by prediction of microstructural evolution in Al 6061-T6. Production of nanostructured metals by large plastic deformation is predicted. Abstract: Severe plastic deformation (strains > 100%) has been shown to create significant grain refinement in polycrystalline materials, leading to a nanometric equiaxed crystalline structure for such metals as aluminum, copper and nickel alloys. This process, termed continuous dynamic recrystallization, is governed by evolution of the dislocation structure, which creates new grain boundaries from dislocation walls. In the proposed model, plasticity occurs which firstly involves dislocation multiplication, leading to strain hardening limited by dynamic recovery. After a critical dislocation density is reached new grain boundaries are formed by condensation of walls of dislocations, creating a new stable configuration that is favored due to a reduction of the system free energy. This evolution of the microstructure continues to develop, with a consequent progressive decrease in the average grain diameter. The proposed model provides a quantitative prediction of the evolution of the average grain size, as well as the dislocation density, during continued plastic strain. The model can be calibrated by use of results from any experiment that involves large plastic deformation of metals, subject to negligible annealing effects. In this paper, the model has been calibrated, and consequently validated, through experiments on machining of Al 6061-T6.